Hypothalamic Regulation of Obesity - Rodríguez-Rodríguez, Rosalía; Miralpeix, Cristina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The manuscripts published in this reprint provide new insights into the hypothalamic neuronal and non-neuronal pathways involved in the pathophysiology and development of obesity and related diseases such as diabetes. Via four original papers, six review manuscripts, and one perspective, this reprint will substantially contribute to the identification of novel therapeutic targets in the hypothalamus and novel approaches to combatting the progression of human obesity.